Analisis Determinan Tarif Angkutan Barang di Pelabuhan Bungkutoko Kendari - Puteri Nabila Pagala; Eliyanti Agus Mokodompit (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2026)
This study aims to analyze the factors that affect the determination of freight transportation rates at Bungkutoko Kendari Port. The research method used is a literature study by examining scientific articles, shipping regulations, and sea transportation policies that apply in Indonesia. The analysis was carried out in a descriptive-qualitative manner to identify and examine the main variables that affect the formation of tariffs. The results of the study show that the determination of freight transportation tariffs is influenced by ship operational costs, shipping distance and travel time, port infrastructure conditions, volume and types of goods, government policies, and fuel price fluctuations, where operational costs and government policies are the dominant factors. In addition, the imbalance between the demand and supply of sea transportation services also contributes to the variation in tariffs at Bungkutoko Kendari Port. These findings recommend the need to improve operational efficiency, improve port infrastructure, and adjust adaptive and transparent tariff policies to create a more efficient, competitive, and sustainable freight tariff system.